Digital Forensic Analysis using Android Application Cache Data - Kim, Hyungchan; Kim, Donghyun; Jo, Wooyeon; Shon, Taeshik (2019 International Conference on Platform Technology and Service, PlatCon 2019 - Proceedings, 2019)
When we use an application on Android, cache data is generated. This can be an important clue to the investigation and needs analysis. However, the present analysis is performed without understanding the generation principle of various cache artifacts, such as purpose and structure, and the data obtained through this simple analysis is used only indirectly for investigation because of lack of information. Therefore, in this paper, we expect to improve the usability of cache by analyzing the type, meaning, and structure of the cache that is stored when the application is used and suggesting an analysis method according to each cache.
Keywords: Analysis method; android; Android applications; Digital forensic analysis; Disk cache; Generation principles; journal; Simple analysis; android; application; digital forensics; disk cache; journal; memory cache